Friday

November 28, 2014

November 28, 2014

Posted by **ct** on Thursday, December 22, 2011 at 7:19pm.

- math -
**Reiny**, Thursday, December 22, 2011 at 8:03pmI will assume you meant

y = tan (x^2) / (1 + cosx)

by quotient rule,

dy/dx = ( (1+cosx)(sec^2 (x^2))(2x) - tan x^2 (-sinx) )/(1+cosx)^2

I don't know what level of simplification you need

y = e^(x^3) - tan 6x

dy/dx = (3x^2)e^(x^3) - 6 sec^2 (6x)

**Answer this Question**

**Related Questions**

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

maths - trigonometry - I've asked about this same question before, and someone ...

Math 12 - Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...

precal - 1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-...

Mathematics - Trigonometric Identities - Prove: sinx + tanx = tanx (1 + cosx) ...

Math - Proving identity (sinx+tanx)/(cosx+1)=tanx RS: (sinx+(sinx/cosx))/(cosx+1...

Math - Im really struggling with these proving identities problems can somebody ...

Trigonometry - Given that a^2+b^2=2 and that (a/b)= tan(45degee+x), find a and b...